PERBEDAAN UKURAN ANTROPOMETRI BAYI DILAHIRKAN IBU ANEMIA DAN IBU TIDAK ANEMIA (Studi Kasus pada Ibu Melahirkan di RSU RA Kartini Jepara) - Wulandari . Meikawatit (Jurnal Kesehatan Masyarakat Indonesia, 2003)
ABSTRACT Background: Anemia is something which very often occurs in society, especially in developing countries in Indonesia. Anemia case is oftentimes found in pregnant women. Anemia in pregnant women is mostly nutrition anemia particularly ferrum deficiency. Based on survey data regarding household health, percentage anemia which is still high result in bad impact toward individu at or society because the human quality and social economy decrease and hampers country development. Objective : to analyze the differences of anthropometric measure of infant born by pregnant woman with anemia and without anemia. Method : This research is implemented in RSU R.A Kartini Jepara since September to October 1998 with survey research. Samples of this research is o mother, either anemia- infected and an anemia uninfected, who gives birth a mature infant in RSU R A Kartini since September to October 1998. Data collected in this research includes respondent identity, infant antropometric measure and Hb degree of a pregnant mother. Data is collected and analyzed by independent samples T test. Conclusion : There is difference between infant weight born by an anemia- infected mother and an anemia-uninfected mother, while infant length size, upper arm circle and head circle indicate that there is no difference between infant born by an anemia- infected mother and an anemia-uninfected mother. Key words: Anthropometry, infant, pregnant, anemia